Child and Adolescent Exposure to Sexual Harassment: Relationship to Gender, Contact Sexual Abuse, and Adult Psychological Symptoms - Briere, John (Journal of interpersonal violence, 2024)
In contrast to adults, there is considerably less research on childhood or adolescent exposure to sexual harassment (CAESH), its lasting psychological correlates, and whether such experiences should be included in definitions of childhood sexual abuse. The current study examined the prevalence and symptomatic sequels of unwanted flirting, being “checked out” sexually, unwanted sexual attention, sexual comments, propositions, and related noncontact behaviors that occurred before age 18, as well as the multivariate relationship between CAESH and contact child sexual abuse (C-CSA) in a diverse online sample of 528 individuals. CAESH was very common, with over 95% of women and 64% of men reporting at least one experience of noncontact sexual harassment before age 18. When childhood sexual abuse was operationalized as the presence of either C-CSA or a total CAESH score of 18 or higher (corresponding to an average score of “3–5 times” prior to age 18), the prevalence was 67% for women and 26% for men, more than three times higher than C-CSA alone. This expanded definition was associated with significantly more anxiety, depression, and posttraumatic stress relative to C-CSA alone. These results suggest that CAESH is a significant source of symptoms in adults and support the emerging perspective that childhood sexual abuse may be best understood as including both contact and noncontact events.